2021
DOI: 10.1002/hsr2.241
|View full text |Cite
|
Sign up to set email alerts
|

Rate of use and effectiveness of oseltamivir in the treatment of influenza illness in high‐risk populations: A systematic review and meta‐analysis

Abstract: Background Oseltamivir is recommended in the treatment of influenza illness in high‐risk populations, including those with chronic heart and lung diseases. Objectives We conducted a systematic review and meta‐analysis to determine the rate of use and effectiveness of oseltamivir in these groups of patients. Methods The protocol for the systematic review was registered on PROSPERO (CRD42019125998). Medline, EMBASE, Cochrane CENTRAL, and CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…8,10 Previous pairwise meta-analyses, including no more than nine studies, have evaluated the effects of oseltamivir on influenza and reported that, compared to standard care or placebo, oseltamivir might reduce hospitalization. 18,44 The results differed from our findings mainly because the previous meta-analyses only included studies published before 2014. Another more recent meta-analysis including 12 studies with 6295 outpatients patients reported that oseltamivir may not be associated with reduced risk of hospitalization and may associated with increased nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 99%
“…8,10 Previous pairwise meta-analyses, including no more than nine studies, have evaluated the effects of oseltamivir on influenza and reported that, compared to standard care or placebo, oseltamivir might reduce hospitalization. 18,44 The results differed from our findings mainly because the previous meta-analyses only included studies published before 2014. Another more recent meta-analysis including 12 studies with 6295 outpatients patients reported that oseltamivir may not be associated with reduced risk of hospitalization and may associated with increased nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 99%
“…Higher treatment rates (e.g., 20%-40%) have been recorded in studies of special populations, such as hospitalized patients, older adults in residential care settings, and children with chronic medical conditions. 19,20 Antiviral treatment among university students may represent an avenue for additional intervention given recommendations to consider using influenza antivirals for postexposure prophylaxis to prevent infection in communal settings (e.g., shelters, university dormitories, and prisons) and reduce strain on healthcare services in these settings during influenza outbreaks. 21 Our findings are subject to at least five limitations.…”
Section: Resultsmentioning
confidence: 99%
“…Although more than half of respondents reported contact with someone with ARI during the week before their clinic visit and almost a third reported specifically having a residential contact with ARI, only 7% reported being prescribed oseltamivir after presenting for testing. Higher treatment rates (e.g., 20%–40%) have been recorded in studies of special populations, such as hospitalized patients, older adults in residential care settings, and children with chronic medical conditions 19,20 . Antiviral treatment among university students may represent an avenue for additional intervention given recommendations to consider using influenza antivirals for post‐exposure prophylaxis to prevent infection in communal settings (e.g., shelters, university dormitories, and prisons) and reduce strain on healthcare services in these settings during influenza outbreaks 21…”
Section: Discussionmentioning
confidence: 99%
“…77,78 A recent meta-analysis has shown that early treatment with oseltamivir is effective in reducing the severity of influenza illness in people with chronic cardio-respiratory disease. 79 There is a paucity of RCT evidence regarding the effect of oseltamivir in ICU patients admitted with severe influenza. In the absence of strong evidence from RCTs involving critically ill patients, observational studies have been relied upon to inform treatment recommendations in severe influenza.…”
Section: Neuraminidase Inhibitorsmentioning
confidence: 99%
“…77 78 A recent meta-analysis has shown that early treatment with oseltamivir is effective in reducing the severity of influenza illness in people with chronic cardio-respiratory disease. 79…”
Section: Drug Therapiesmentioning
confidence: 99%